2017
DOI: 10.3399/bjgp17x690917
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer in symptomatic patients presenting in primary care: a systematic review of risk prediction tools

Abstract: There is insufficient evidence for the recommendation of any one of the available risk prediction tools. However, some multivariable tools showed promising discrimination. What is needed to guide clinical practice is both external validation of the existing tools and a comparative study, so that the best tools can be incorporated into clinical decision tools used in primary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 22 publications
(70 reference statements)
0
12
0
Order By: Relevance
“…In this study, we aim to determine the validity of symptom-based lung cancer diagnosis, using published studies, routine data from electronic health records and published prior risk models. A recent review of lung cancer diagnosis using ‘Risk Assessment Tools’ (RATs) found that there was insufficient validation, and that the inclusion of ‘epidemiological risk factors’ in the models, along with symptoms, created confounders [ 5 ]. In this review, we specifically assess symptoms associated with lung cancer diagnosis without epidemiological factors, to avoid confounding.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we aim to determine the validity of symptom-based lung cancer diagnosis, using published studies, routine data from electronic health records and published prior risk models. A recent review of lung cancer diagnosis using ‘Risk Assessment Tools’ (RATs) found that there was insufficient validation, and that the inclusion of ‘epidemiological risk factors’ in the models, along with symptoms, created confounders [ 5 ]. In this review, we specifically assess symptoms associated with lung cancer diagnosis without epidemiological factors, to avoid confounding.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar review, looking at risk prediction models for screening, Usher-Smith and colleagues (2015) [ 53 ] concluded that, even though some of the colorectal cancer prediction models had potential for clinical application, there remains considerable uncertainty about their clinical utility. Similarly, Schmidt-Hansen and colleagues (2017) [ 58 ] conducted a review of lung cancer tools and found limited evidence to support the recommendation of any of the identified risk prediction tools, due to lack of external validation or cost impact assessment.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published systematic review of risk prediction tools for patients with LC based on UK primary care data compared five different tools. 38 There was not sufficient evidence to recommend any of them because of the lack of external validation, evaluation in clinical practice, and cost impact. Also, none of the tools differentiated between symptoms depending on tumour stage.…”
Section: Discussionmentioning
confidence: 99%